2022
DOI: 10.9734/ijpss/2022/v34i1631015
|View full text |Cite
|
Sign up to set email alerts
|

Study of Release Pattern of Phosphorus in Soils: Incubated with Organic Acids and Different Origin of Rock Phosphate

Abstract: In this study the hypotheses assumed was assessed through incubation study in lab. Soil samples were pre incubated at 25 °C for 1 week prior to actual incubation to stabilize the microbial activity. Moisture content of soil was adjusted to 60 % of water holding capacity by adding deionized water. There were three Rock Phosphates of origin Jhabua, Udaipur-I, Udaipur-II and eleven treatments including the control and soils were analysed at six incubation periods (15, 30, 45, 60, 90 and 120 days); with three repl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
1
1
0
Order By: Relevance
“…In a similar study of Mahawar [54] it was observed that with the application rock phosphate the quantity of P available in soil was high for more than 60 days. The studies of SanthoshKumar [55] and Jalali and Ranjbar [56] also put forward similar results regarding rockphosphate.…”
Section: Soil Available Phosphoroussupporting
confidence: 55%
“…In a similar study of Mahawar [54] it was observed that with the application rock phosphate the quantity of P available in soil was high for more than 60 days. The studies of SanthoshKumar [55] and Jalali and Ranjbar [56] also put forward similar results regarding rockphosphate.…”
Section: Soil Available Phosphoroussupporting
confidence: 55%
“…With increasing cultivation time, H + in organic acid was fully released, and the more phosphate in phosphate ore powder was in contact with H + , the greater its solubility (Mahawar et al, 2022). At the same time, there may be an exchange of organic anions in the active mineral with phosphate particles in the phosphate ore powder to achieve phosphorus release (Na, 2020), making the P2O5 content in the phosphate ore powder gradually increase within 6 days of activation cultivation.…”
Section: Activation Culture Timementioning
confidence: 99%